The Examination of Sports Club Managers' Attitudes toward Healthy Nutrition - Atali, Levent; Tarim, Tahir; Altuntaş , Talha; Atali, Makbule (Progress in Nutrition, 2021)
Study Objectives: This study aimed to examine the attitudes of amateur sports club managers toward healthy nutrition in different variables. Method: The study's data was obtained using the Attitude toward Healthy Nutrition Scale, which has 21 elements and four sub-dimensions. The t-test was used to examine the difference between the obtained ATHNS dimensions according to gender and nutritional education. The analysis of variance (ANOVA) test was used to examine the study's dimensions according to education, age, and monthly income level, and the Sidak test for paired comparisons. Results:  The attitude toward healthy nutrition (ATHN), feeling toward nutrition (FTN), positive nutrition (PN), and malnutrition (MN) levels of the female and male participants were similar (p> 0.05). In the study, it was found that (ATHN) levels of some age groups were lower than the participants in other age groups (p